A modified preparation method for an embedded mesophase asphalt-based silicon-carbon composite electrode material

By using mosaic mesophase as a carbon source, combined with hydrothermal reaction and magnesium thermal reduction technology, a silicon-carbon composite electrode material with a quadratic structure of "carbon-vacuum-silicon-carbon" was prepared, which solved the structural problems caused by volume changes in the silicon anode material during circulation, and achieved high rate performance and high reversible specific capacity battery performance.

CN115458726BActive Publication Date: 2025-03-07CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211257368.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-14
Publication Date
2025-03-07
Estimated Expiration
2042-10-14

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the silicon anode material has a structural collapse and repeated regeneration of the solid electrolyte interface (SEI) film due to volume changes during the circulation process, and its inherent electrical conductivity is insufficient, resulting in low utilization of active particles and poor fast charging capabilities.

Method used

By using mosaic mesophase as a carbon source, combined with hydrothermal reaction and magnesium thermal reduction technology, a silicon-carbon composite electrode material with a quadratic structure of "carbon-vacuum-silicon-carbon" was prepared. This method improves the electrochemical properties of the material by strictly controlling the reaction conditions to ensure irregular orientation of the carbon layer and uniform deposition of silicon.

Benefits of technology

High-rate performance and high reversible specific capacity are achieved, the first-round Coulomb efficiency is above 70%, the reversible specific capacity is above 550mAh/g at 0.1C current density, and the specific capacity is above 400mAh/g at 10C high current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115458726B_ABST
    Figure CN115458726B_ABST
Patent Text Reader

Abstract

The invention discloses a modified preparation method of a mosaic mesophase asphalt-based silicon-carbon composite electrode material, using a petroleum-based mosaic mesophase asphalt as a carbon source and an oxygen-containing organosilicon compound as a silicon source, obtaining a preliminary composite product through hydrothermal reaction and magnesium thermal reduction, and then using calcium carbonate as a sacrificial layer, and the mosaic mesophase asphalt as both an outer coating layer and an inner core, to prepare a silicon-carbon composite electrode material with a "carbon-void-silicon-carbon" four-level core-shell structure. The structure of the mosaic mesophase asphalt allows lithium ions to be quickly embedded between carbon layers from all directions during high-current charge and discharge, and has a high rate performance. The first-cycle coulomb efficiency of the composite electrode material finally obtained is above 70%, the reversible specific capacity at a current density of 0.1C is above 550mAh / g, and the specific capacity at a high current density of 10C is above 400mAh / g, and it has the advantages of good conductivity, good rate performance, and stable cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery electrode materials and relates to a modification preparation method of a silicon-carbon composite electrode material. Background Art

[0002] Lithium-ion batteries (LIBs) have become a hot topic in research and application in recent decades due to their high energy density, high rate performance and environmental protection. In practical applications, the mainstream commercial graphite anode material has a theoretical specific capacity (372 mAh / g), which is far from meeting the high energy density requirements of high-tech equipment such as pure electric vehicles. Silicon has become a very promising candidate material due to its high theoretical specific capacity (4200 mAh / g), low lithium insertion potential, high natural abundance, and recyclable high-purity silicon in the photovoltaic industry. However, during the cycle process, high specific capacity also means drastic volume changes (silicon volume expansion and contraction up to 300%), which directly leads to severe structural collapse of active silicon particles and repeated regeneration of solid electrolyte interface (SEI) film. In addition, the semiconductor properties of silicon limit its inherent conductivity, resulting in low utilization of active particles and poor fast charging capability. In order to mitigate the volume effect and improve conductivity, many strategies for designing silicon-based anode materials have been proposed. Among them, silicon-carbon composites, as one of the most successful strategies, are being widely studied. However, most of the research on silicon-carbon composites focuses on the structural engineering of silicon particles, such as core-shell structures, hollow spheres, three-dimensional (3D) porous structures, and yolk-shell structures. In fact, few studies focus on the inherent nature of carbon components in the structural design of silicon-carbon composites, and it is crucial to study the microstructure of carbon components and their electrochemical behavior, and fundamentally understand how the microstructure of carbon in silicon / carbon composites affects battery performance.

[0003] Pitch is a good carbon source for preparing high-performance silicon / carbon composites. Pitch-derived soft carbon materials have the advantages of controllable crystallinity, outstanding electron transfer properties and structural elasticity. In addition, the pore channels and topological defects of soft carbon can be easily adjusted by heat treatment temperature to achieve ion diffusion and electronic compatibility. However, the properties of active silicon particles and their requirements for carbon components are very different from traditional graphite. The type of pitch and pyrolysis temperature have a great influence on the microstructure of soft carbon compounds, which will be a potential way to optimize the electrochemical performance of active silicon. By definition, mesophase pitch is an anisotropic substance in a large area generated by heavy aromatic hydrocarbons during heat treatment, and its structural morphology can generally be divided into mosaic type, streamlined type, etc. The present invention innovatively uses mosaic mesophase pitch as a carbon source to prepare a silicon-carbon composite electrode material with good performance. Summary of the invention

[0004] In order to overcome the shortcomings of the prior art, the present invention strictly controls the reaction conditions, uses the mosaic-type mesophase asphalt as the carbon source, and prepares a silicon-carbon composite material as the inner core through hydrothermal reaction and magnesium thermal reduction. Calcium carbonate is used as a sacrificial layer and the mosaic-type mesophase asphalt is used as a coating layer to successfully prepare a silicon-carbon composite electrode material with a quaternary structure of "carbon-void-silicon-carbon" with high rate performance.

[0005] The object of the present invention is achieved through the following technical solutions:

[0006] A modified preparation method of an embedded mesophase pitch-based silicon-carbon composite electrode material comprises the following specific steps:

[0007] Step 1: Weigh a certain amount of mosaic mesophase pitch and perform ball milling at a mass ratio of 1:20, using zirconium oxide balls as the ball milling medium, immerse the ball-milled mosaic mesophase pitch in a 5-10 mol / L organic strong alkali solution, and vigorously stir at 160°C-220°C for 4 hours to obtain a mosaic mesophase pitch activated by the alkali solution;

[0008] The organic strong base is one of potassium tert-butoxide, sodium tert-butoxide or tetramethylguanidine;

[0009] Step 2: The mosaic mesophase asphalt activated by the alkaline solution is washed with deionized water until it is neutral and ultrasonically dispersed in a certain amount of deionized water / ethanol mixed solution, and the oxygen-containing organosilicon compound is added dropwise under ultrasound; then the ultrasonicated solution is transferred to a hydrothermal reactor, reacted at 160-200° C. for 6-15 hours, the hydrothermal reaction product is filtered, and the precipitate is washed three times with ethanol and deionized water respectively, and dried in an oven to obtain a dry product;

[0010] The oxygen-containing organosilicon compound is selected from one of triisopropylsilyl trifluoromethanesulfonate, 3-tert-butyldimethylsilyl-2-propyn-1-ol or (1,1-dimethylethyl)dimethylsilyl trifluoromethanesulfonate;

[0011] Step 3: The dried product is mixed with Mg powder in a mass ratio of 10:1, reacted at 600°C in an argon / hydrogen mixture for 4-8 hours, and the obtained mixture is washed with dilute hydrochloric acid, ethanol and deionized water respectively until neutral, and dried to obtain a treated magnesium thermal reaction product;

[0012] Step 4: Ultrasonic dispersion of the treated magnesium thermal reaction product in deionized water, adding a certain amount of sodium carbonate and calcium chloride in turn, stirring vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then adding the white precipitate to a certain amount of mosaic mesophase asphalt solution, stirring for 24 hours, filtering, washing with deionized water and drying; placing the dried precipitate in a tubular furnace, pre-oxidizing at 300°C in air atmosphere for 2-4 hours, and carbonizing at 800-1000°C in argon atmosphere for 2 hours to obtain a carbonized product;

[0013] Step 5: Place the carbonized product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain an embedded intermediate phase asphalt-based silicon-carbon composite electrode material having a four-level core-shell structure of "carbon-void-silicon-carbon".

[0014] In the present invention, the silicon content of the electrode material is controlled by the amount of oxygen-containing organosilicon compounds added in the hydrothermal synthesis raw materials. The more oxygen-containing organosilicon compounds are added, the higher the silicon content in the final product. The ratio of the embedded mesophase asphalt to the oxygen-containing organosilicon compounds after ball milling is 1g: (0.2-0.6)g.

[0015] In the present invention, the cavity thickness of the electrode material is related to the mass of the sodium carbonate and calcium chloride added in step 4 and the magnesium thermal reaction product obtained in step 3. Preferably, the molar ratio of sodium carbonate to calcium chloride is 1:1, and the mass ratio of the magnesium thermal reaction product to sodium carbonate is 3:1.

[0016] In the present invention, the mosaic mesophase asphalt is a coarse-grained mosaic petroleum-based mesophase asphalt, which means that the radius of the anisotropic substances in the asphalt is distributed between 5 and 8 microns, and more preferably, the average anisotropic radius is 7.5 microns.

[0017] In the present invention, the method for preparing the solution of the mosaic mesophase asphalt is to dissolve the mosaic mesophase asphalt in a solvent, wherein the solvent is selected from one or more of tetrahydrofuran, toluene, N-methylpyrrolidone, and pyridine; the amount ratio of the solvent to the mosaic mesophase asphalt is 200mL: (0.5-1.5)g.

[0018] In step 4 of the present invention, the heating rate of the air atmosphere pre-oxidation process is 1°C / min.

[0019] In the present invention, in the embedded mesophase pitch-based silicon-carbon composite electrode material, the thickness of the silicon layer is 0.03-0.1 μm, the thickness of the void structure is 0.02-0.1 μm, and the thickness of the external carbon layer is 0.02-0.1 μm.

[0020] The present invention also provides an embedded mesophase asphalt-based silicon-carbon composite electrode material prepared by the above method, which has a four-level core-shell structure of "carbon-void-silicon-carbon", a first-cycle coulomb efficiency of more than 70%, a reversible specific capacity of more than 550 mAh / g at a current density of 0.1C, and a specific capacity of more than 400 mAh / g at a high current density of 10C.

[0021] The classification of mesophase asphalt is determined based on the size of the monochromatic area presented by the anisotropic substance in the mesophase asphalt under orthogonal polarized light, wherein the radius distribution of the anisotropic substance in the asphalt is below 10 microns is called "mosaic" mesophase asphalt. In particular, the present invention selects a coarse-grained mosaic asphalt with an anisotropic substance radius distribution between 5-8 microns and an average anisotropic radius of 7.5 microns, which has the best rate performance, exhibits irregular orientation of the basic building units of the carbon layer at the microscopic level, and presents a long-range disordered state under a polarizing microscope. This irregular orientation of a large number of carbon layers allows lithium ions to be quickly embedded between the carbon layers from all directions during high current charging and discharging, so that the mosaic mesophase asphalt material has a higher rate performance. The hydrothermal reaction process of silicone makes silicon deposit evenly on the surface of the carbon substrate, promoting the close bonding between the two; calcium carbonate is then used as a sacrificial layer to introduce a void structure into the structure. Compared with the traditional carbon-coated silicon secondary structure, the introduction of the void structure reserves sufficient volume expansion space for silicon, and the outermost layer is again coated with embedded intermediate phase asphalt, which effectively limits the excessive expansion of silicon. In this way, a silicon-carbon composite lithium-ion battery electrode material with high rate performance was successfully prepared.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] 1. The carbon matrix in the composite material is a mosaic mesophase pitch prepared from heavy oil, which has the advantages of wide sources and low prices. In addition, the mosaic structured pitch has a higher rate performance due to the irregularity of its carbon layer orientation.

[0024] 2. The carbon precursor is activated by a strong alkaline solution, which increases the oxygen-containing functional groups on the mesophase asphalt and promotes the combination of carbon and silicon during the composite process.

[0025] 3. Using organic silicon as the silicon source, the silicon-containing components are adsorbed onto the carbon substrate through electrostatic action, and then reduced through a one-step magnesium thermal reaction. Compared with mechanical mixing, the combination of silicon and carbon is tighter.

[0026] 4. Calcium carbonate is used as a sacrificial layer to facilitate etching and reserve sufficient space for the volume expansion of the inner silicon layer; and the outermost coating carbon layer further restricts the expansion of silicon. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a polarized photo of the mosaic mesophase pitch used in the present invention.

[0028] Figure 2 It is a schematic structural diagram of the embedded mesophase asphalt-based silicon-carbon composite electrode material prepared by the present invention. DETAILED DESCRIPTION

[0029] In order to make the modification and preparation method of the embedded mesophase pitch-based silicon-carbon composite electrode material of the present invention more understandable, it is described below in conjunction with embodiments.

[0030] Embodiment 1:

[0031] Step 1: Weigh a certain amount of mosaic mesophase pitch and mix it with 20g of zirconium oxide balls, rotate at 800rpm, and ball mill for 8h; immerse 1g of the ball-milled mosaic mesophase pitch in 200ml of 5mol / L potassium tert-butoxide solution, stir vigorously at 160℃ for 4h to obtain the mosaic mesophase pitch activated by alkaline solution;

[0032] Step 2: The mosaic mesophase asphalt activated by the alkaline solution is washed with deionized water until it is neutral and ultrasonically dispersed in 200 ml of a deionized water / ethanol mixed solution (deionized water: ethanol = 1:1, mass ratio), and 20 ml of a triisopropylsilyl trifluoromethanesulfonate ethanol solution with a mass concentration of 0.01 g / ml is added dropwise under ultrasound, and ultrasound is continued until it is completely dispersed; the solution after ultrasound is transferred to a hydrothermal reactor, reacted at 160° C. for 8 hours, the hydrothermal reaction product is filtered, and the precipitate is washed three times with ethanol and deionized water respectively, and placed in an oven at 80° C. for 24 hours to obtain a dry product;

[0033] Step 3: 1.1 g of the dried product was mixed with 0.11 g of Mg powder, and reacted at 600° C. for 4 h in an argon / hydrogen mixture. The obtained mixture was washed with 0.1 mol / L dilute hydrochloric acid, ethanol and deionized water to neutrality, and dried to obtain a treated magnesium thermal reaction product;

[0034] Step 4: Ultrasonic dispersion of 1 g of the treated magnesium thermal reaction product in deionized water, and sequentially adding 0.32 g of sodium carbonate and 0.33 g of calcium chloride, stirring vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then adding the white precipitate to a 200 ml toluene solution of 0.5 g of mosaic mesophase asphalt, stirring for 24 h, filtering, washing with deionized water and drying; placing the dried precipitate in a tubular furnace, pre-oxidizing at 300 ° C in an air atmosphere for 2 h, and carbonizing at 850 ° C in an argon atmosphere for 2 h to obtain a carbonized product;

[0035] Step 5: Place the carbonized product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain an embedded intermediate phase asphalt-based silicon-carbon composite electrode material A, which has a four-level core-shell structure of "carbon-void-silicon-carbon", wherein the thickness of the silicon layer is 0.05 μm, the thickness of the void structure is 0.025 μm, and the thickness of the outer carbon layer is 0.05 μm.

[0036] Embodiment 2:

[0037] Step 1: Weigh a certain amount of mosaic mesophase pitch and mix it with 20g of zirconium oxide balls, rotate at 800rpm, and ball mill for 8h. Immerse 1g of the ball-milled mosaic mesophase pitch in 200ml of 5mol / L potassium tert-butoxide solution, and stir vigorously at 160°C for 4h to obtain the mosaic mesophase pitch activated by alkaline solution;

[0038] Step 2: The mosaic mesophase asphalt activated by the alkaline solution is washed with deionized water until it is neutral and ultrasonically dispersed in 200 ml of a deionized water / ethanol mixed solution (deionized water: ethanol = 1:1, mass ratio), and 30 ml of a triisopropylsilyl trifluoromethanesulfonate ethanol solution with a mass concentration of 0.01 g / ml is added dropwise under ultrasound, and ultrasound is continued until it is completely dispersed; the ultrasonicated solution is transferred to a hydrothermal reactor and reacted at 160° C. for 12 hours; the hydrothermal reaction product is filtered, and the precipitate is washed three times with ethanol and deionized water respectively, and dried in an oven at 80° C. for 24 hours to obtain a dry product;

[0039] Step 3: 1.2 g of the dried product was mixed with 0.12 g of Mg powder, and reacted in an argon / hydrogen mixture at 600° C. for 4 h; the obtained mixture was washed with 0.1 mol / L dilute hydrochloric acid, ethanol and deionized water respectively until neutral, and dried to obtain the treated magnesium thermal reaction product.

[0040] Step 4: ultrasonically disperse 1 g of the treated magnesium thermal reaction product in deionized water, add 0.32 g of sodium carbonate and 0.33 g of calcium chloride in sequence, and stir vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then add the white precipitate to 200 ml of toluene solution of 0.5 g of mosaic mesophase asphalt, stir for 24 h, filter, wash with deionized water and dry; place the dried precipitate in a tubular furnace, pre-oxidize at 300 ° C in air atmosphere for 2 h, and carbonize at 1000 ° C in argon atmosphere for 2 h to obtain a carbonized product;

[0041] Step 5: Place the carbonized product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain an embedded intermediate phase asphalt-based silicon-carbon composite electrode material B, which has a four-level core-shell structure of "carbon-void-silicon-carbon", wherein the thickness of the silicon layer is 0.05 μm, the thickness of the void structure is 0.06 μm, and the thickness of the outer carbon layer is 0.05 μm.

[0042] Embodiment 3:

[0043] Step 1: Weigh a certain amount of mosaic mesophase pitch and mix it with 20g of zirconium oxide balls, rotate at 800rpm, and ball mill for 8h. Immerse 1g of the ball-milled mosaic mesophase pitch in 200ml of 5mol / L potassium tert-butoxide solution, and stir vigorously at 160°C for 4h to obtain the mosaic mesophase pitch activated by alkaline solution;

[0044] Step 2: The mosaic mesophase asphalt activated by the alkaline solution is washed with deionized water until it is neutral and ultrasonically dispersed in 200 ml of a deionized water / ethanol mixed solution (deionized water: ethanol = 1:1, mass ratio), and 30 ml of a 3-tert-butyldimethylsilyl-2-propyn-1-ol ethanol solution with a mass concentration of 0.01 g / ml is added dropwise under ultrasound, and ultrasound is continued until it is completely dispersed; the solution after ultrasound is transferred to a hydrothermal reactor, reacted at 160° C. for 12 hours, the hydrothermal reaction product is filtered, and the precipitate is washed three times with ethanol and deionized water respectively, and placed in an oven at 80° C. for 24 hours to obtain a dry product;

[0045] Step 3: 1.2 g of the dried product was mixed with 0.12 g of Mg powder, and reacted at 600° C. for 4 h in an argon / hydrogen mixture. The obtained mixture was washed with 0.1 mol / L dilute hydrochloric acid, ethanol and deionized water respectively until neutral, and dried to obtain a treated magnesium thermal reaction product;

[0046] Step 4: ultrasonically disperse 1 g of the treated magnesium thermal reaction product in deionized water, add 0.32 g of sodium carbonate and 0.33 g of calcium chloride in sequence, and stir vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then add the obtained white precipitate to 200 ml of toluene solution of 0.5 g of mosaic mesophase asphalt, stir for 24 h, filter, wash with deionized water and dry; place the dried precipitate in a tubular furnace, pre-oxidize at 300 ° C in air atmosphere for 2 h, and carbonize at 1000 ° C in argon atmosphere for 2 h to obtain a carbonized product;

[0047] Step 5: Place the carbonized product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain an embedded intermediate phase asphalt-based silicon-carbon composite electrode material C, which has a four-level core-shell structure of "carbon-void-silicon-carbon", wherein the thickness of the silicon layer is 0.05 μm, the thickness of the void structure is 0.02 μm, and the thickness of the external carbon layer is 0.05 μm.

[0048] Embodiment 4:

[0049] Step 1: Weigh a certain amount of mosaic mesophase pitch and mix it with 20g of zirconium oxide balls, rotate at 800rpm, and ball mill for 8h. Immerse 1g of the ball-milled mosaic mesophase pitch in 200ml of 5mol / L potassium tert-butoxide solution, and stir vigorously at 160°C for 4h to obtain the mosaic mesophase pitch activated by alkaline solution;

[0050] Step 2: The mosaic mesophase asphalt activated by the alkaline solution is washed with deionized water until it is neutral and ultrasonically dispersed in 200 ml of a deionized water / ethanol mixed solution (deionized water: ethanol = 1:1, mass ratio), and 30 ml of a 3-tert-butyldimethylsilyl-2-propyn-1-ol ethanol solution with a mass concentration of 0.01 g / ml is added dropwise under ultrasound, and ultrasound is continued until it is completely dispersed; the solution after ultrasound is transferred to a hydrothermal reactor, reacted at 160° C. for 12 hours, the hydrothermal reaction product is filtered, and the precipitate is washed three times with ethanol and deionized water respectively, and placed in an oven at 80° C. to dry for 24 hours to obtain a dry product;

[0051] Step 3: 1.2 g of the dried product was mixed with 0.12 g of Mg powder, and reacted at 600° C. for 4 h in an argon / hydrogen mixture. The obtained mixture was washed with 0.1 mol / L dilute hydrochloric acid, ethanol and deionized water respectively until neutral, and dried to obtain a treated magnesium thermal reaction product;

[0052] Step 4: Add 1 g of the treated magnesium thermal reaction product to 200 ml of toluene solution of 0.5 g of mosaic mesophase asphalt, stir for 24 hours, filter, wash with deionized water and dry; place the dried precipitate in a tubular furnace, pre-oxidize at 300°C in an air atmosphere for 2 hours, and carbonize at 1000°C in an argon atmosphere for 2 hours to obtain a mosaic mesophase asphalt-based silicon-carbon composite electrode material D, which has a three-level core-shell structure of "carbon-silicon-carbon", wherein the thickness of the silicon layer is 0.05 μm and the thickness of the outer carbon layer is 0.05 μm.

[0053] Embodiment 5:

[0054] This embodiment provides a modification preparation method of a petroleum coke-based silicon-carbon composite electrode material. The raw material petroleum coke used is Grade I petroleum coke that complies with GB / T 24533-2019, and its technical indicators are shown in Table 1.

[0055] Table 1 Main technical indicators of Grade I petroleum coke

[0056]

[0057] Step 1: Weigh a certain amount of petroleum coke and mix it with 20g of zirconium oxide balls, rotate at 800rpm, and ball-mill for 8h. Immerse 1g of the ball-milled petroleum coke in 200ml of 7mol / L potassium tert-butoxide solution, and stir vigorously at 160℃ for 4h to obtain alkaline solution-activated petroleum coke;

[0058] Step 2: Wash the activated petroleum coke with deionized water until it is neutral and ultrasonically disperse it in 200 ml of a deionized water / ethanol mixed solution (deionized water: ethanol = 1:1, mass ratio), dropwise add 60 ml of 3-tert-butyldimethylsilyl-2-propyn-1-ol ethanol solution with a mass concentration of 0.01 g / ml, and continue ultrasonication until it is completely dispersed; transfer the ultrasonicated solution to a hydrothermal reactor, react at 160° C. for 12 hours, filter the hydrothermal reaction product, wash the precipitate with ethanol and deionized water three times respectively, and dry it in an oven at 80° C. for 24 hours to obtain a dry product;

[0059] Step 3: Mix 1.2 g of the dried product with 0.12 g of Mg powder and react at 600°C for 4 h in an argon / hydrogen mixture. Wash the resulting mixture with 0.1 mol / L dilute hydrochloric acid, ethanol, and deionized water until neutral, and dry to obtain the treated magnesium thermal reaction product.

[0060] Step 4: Ultrasonic dispersion of 1 g of the treated magnesium thermal reaction product in deionized water, adding 0.32 g of sodium carbonate and 0.33 g of calcium chloride in sequence, stirring vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then adding the obtained white precipitate to a 200 ml toluene solution of 0.5 g of petroleum coke, stirring for 24 h, filtering, washing with deionized water and drying; placing the dried precipitate in a tubular furnace, pre-oxidizing at 300° C. in an air atmosphere for 2 h, and carbonizing at 1000° C. in an argon atmosphere for 2 h to obtain a carbonized product;

[0061] Step 5: Place the carbonized product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain a "carbon-void-silicon-carbon" four-level core-shell composite silicon-carbon electrode material E, wherein the silicon layer has a thickness of 0.05 μm, the void structure has a thickness of 0.04 μm, and the outer carbon layer has a thickness of 0.1 μm.

[0062] Embodiment 6:

[0063] Step 1: Weigh a certain amount of mosaic mesophase pitch (anisotropic size 0.5-1.5 microns) and mix it with 20g of zirconium oxide balls, rotate at 800rpm, and ball mill for 8h. Immerse 1g of the ball-milled mosaic mesophase pitch in 200ml of 5mol / L potassium tert-butoxide solution, and stir vigorously at 160°C for 4h to obtain the mosaic mesophase pitch activated by alkaline solution;

[0064] Step 2: The mosaic mesophase asphalt activated by the alkaline solution is washed with deionized water until it is neutral and ultrasonically dispersed in 200 ml of a deionized water / ethanol mixed solution (deionized water: ethanol = 1:1, mass ratio), and 30 ml of a 3-tert-butyldimethylsilyl-2-propyn-1-ol ethanol solution with a mass concentration of 0.01 g / ml is added dropwise under ultrasound, and ultrasound is continued until it is completely dispersed; the solution after ultrasound is transferred to a hydrothermal reactor, reacted at 160° C. for 12 hours, the hydrothermal reaction product is filtered, and the precipitate is washed three times with ethanol and deionized water respectively, and placed in an oven at 80° C. for 24 hours to obtain a dry product;

[0065] Step 3: 1.2 g of the dried product was mixed with 0.12 g of Mg powder, and reacted at 600° C. for 4 h in an argon / hydrogen mixture. The obtained mixture was washed with 0.1 mol / L dilute hydrochloric acid, ethanol and deionized water respectively until neutral, and dried to obtain a treated magnesium thermal reaction product;

[0066] Step 4: ultrasonically disperse 1 g of the treated magnesium thermal reaction product in deionized water, add 0.32 g of sodium carbonate and 0.33 g of calcium chloride in sequence, and stir vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then add the obtained white precipitate to 200 ml of toluene solution of 0.5 g of mosaic mesophase asphalt, stir for 24 h, filter, wash with deionized water and dry; place the dried precipitate in a tubular furnace, pre-oxidize at 300 ° C in air atmosphere for 2 h, and carbonize at 1000 ° C in argon atmosphere for 2 h to obtain a carbonized product;

[0067] Step 5: Place the carbonized product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain an embedded intermediate phase asphalt-based silicon-carbon composite electrode material F, which has a four-level core-shell structure of "carbon-void-silicon-carbon", wherein the thickness of the silicon layer is 0.05 μm, the thickness of the void structure is 0.02 μm, and the thickness of the outer carbon layer is 0.05 μm.

[0068] Embodiment 7:

[0069] Step 1: Weigh a certain amount of mosaic mesophase pitch (anisotropic size 1.5-5 microns) and mix it with 20g of zirconium oxide balls, rotate at 800rpm, and ball mill for 8h. Immerse 1g of the ball-milled mosaic mesophase pitch in 200ml of 5mol / L potassium tert-butoxide solution, and stir vigorously at 160°C for 4h to obtain the mosaic mesophase pitch activated by alkaline solution;

[0070] Step 2: The mosaic mesophase asphalt activated by the alkaline solution is washed with deionized water until it is neutral and ultrasonically dispersed in 200 ml of a deionized water / ethanol mixed solution (deionized water: ethanol = 1:1, mass ratio), and 30 ml of a 3-tert-butyldimethylsilyl-2-propyn-1-ol ethanol solution with a mass concentration of 0.01 g / ml is added dropwise under ultrasound, and ultrasound is continued until it is completely dispersed; the solution after ultrasound is transferred to a hydrothermal reactor, reacted at 160° C. for 12 hours, the hydrothermal reaction product is filtered, and the precipitate is washed three times with ethanol and deionized water respectively, and placed in an oven at 80° C. for 24 hours to obtain a dry product;

[0071] Step 3: 1.2 g of the dried product was mixed with 0.12 g of Mg powder, and reacted at 600° C. for 4 h in an argon / hydrogen mixture. The obtained mixture was washed with 0.1 mol / L dilute hydrochloric acid, ethanol and deionized water respectively until neutral, and dried to obtain a treated magnesium thermal reaction product;

[0072] Step 4: ultrasonically disperse 1 g of the treated magnesium thermal reaction product in deionized water, add 0.32 g of sodium carbonate and 0.33 g of calcium chloride in sequence, and stir vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then add the obtained white precipitate to 200 ml of toluene solution of 0.5 g of mosaic mesophase asphalt, stir for 24 h, filter, wash with deionized water and dry; place the dried precipitate in a tubular furnace, pre-oxidize at 300 ° C in air atmosphere for 2 h, and carbonize at 1000 ° C in argon atmosphere for 2 h to obtain a carbonized product;

[0073] Step 5: Place the carbonized product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain an embedded intermediate phase asphalt-based silicon-carbon composite electrode material G, which has a four-level core-shell structure of "carbon-void-silicon-carbon", wherein the thickness of the silicon layer is 0.05 μm, the thickness of the void structure is 0.02 μm, and the thickness of the external carbon layer is 0.05 μm.

[0074] Battery performance test

[0075] 1. Electrode preparation: The electrode material prepared in Example 1-6 was mixed with acetylene black and PVDF in a mass ratio of 8:1:1, ground with NMP (nitromethylpyrrolidone) as solvent to form a uniform slurry and applied on a copper foil, dried at 90°C in vacuum for 24h, and rolled to obtain an electrode sheet.

[0076] 2. Battery performance test: The obtained negative electrode sheet was cut into electrode sheets with a diameter of 12 mm for battery assembly. The assembly process was carried out in a glove box filled with Ar gas, and the water and oxygen content was less than 0.01 ppm. The battery used a CR2032 button cell, with a metal lithium sheet as the counter electrode, a polypropylene film as the diaphragm, and 1M lithium hexafluorophosphate (the solvent was a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1, with 5% fluoroethylene carbonate added) as the electrolyte. The assembled button cell was subjected to a 0.1C charge and discharge cycle performance test and a 10C high current discharge performance test at 25°C and a voltage range of 0.05V-2.2V. The measured battery first cycle specific capacity (mAh / g), first charge and discharge efficiency (%), and reversible cycle specific capacity (mAh / g, 500 cycles) were recorded, and the silicon content in each electrode material was given. The results are shown in Table 2.

[0077] Table 2 Comparison of electrode material performance

[0078]

[0079] It can be seen from the data in Table 2 that compared with the existing graphite negative electrode (360mAh / g), the silicon-carbon composite electrode materials prepared by the method described in Examples 1-3 of the present invention all have higher reversible specific capacity (all above 550mAh / g). In addition, by comparison, it can be found that the first charge and discharge efficiency of the battery increases with the increase of the carbonization temperature of the composite electrode material (850°C for Example 1, 1000°C for Examples 2 and 3). This is because as the carbonization temperature increases, the degree of graphitization of carbon in the composite electrode material gradually increases, and the heteroatom content gradually decreases, avoiding the occurrence of too many side reactions. The final experimental results show that 1000°C is the optimal carbonization temperature. In addition, since too high a Si content will cause a large volume expansion in the electrode material, preferably, about 7% is the optimal silicon content in the composite electrode material. By comparing electrode material C with electrode material D, it can be seen that the silicon-carbon composite electrode material prepared from the same material, due to the introduction of a void structure in electrode material C, can better buffer the volume expansion of silicon inside the material, and the specific capacity is significantly better than electrode material D without a void structure. Comparing electrode material C and electrode material E, when the structure of the prepared silicon-carbon composite material is the same, the specific capacity of the two is similar at a small current of 0.1C, but the electrode material C using the embedded mesophase asphalt shows significantly superior electrochemical performance at a high current of 10C. This is because the electrochemical reaction is accelerated under high current, and the carbon layer with inconsistent internal orientation in the embedded mesophase asphalt allows lithium ions to be quickly deintercalated in different directions, thus showing more excellent performance. By controlling the amount of sodium carbonate and calcium chloride added, void layers of different thicknesses can be prepared, which can be flexibly controlled according to different silicon loadings. Comparing electrode material C with electrode material F and electrode material G, the only difference among the three is the anisotropic size of the embedded mesophase asphalt used. The present invention unexpectedly found that the embedded mesophase asphalt with an anisotropic size in the range of 5-8 microns has the highest specific capacity at current densities of 0.1C and 10C.

Claims

1. A modified preparation method of an embedded mesophase pitch-based silicon-carbon composite electrode material, characterized in that: The specific steps include: Step 1: Weigh a certain amount of mosaic mesophase pitch and mix it with 20g of ball milling medium for ball milling treatment, the ball milling medium is zirconium oxide ball, immerse 1g of the ball-milled mosaic mesophase pitch in a 5-10mol / L organic strong alkali solution, and vigorously stir at 160℃-220℃ for 4h to obtain the mosaic mesophase pitch activated by the alkali solution; Step 2: The mosaic mesophase asphalt activated by the alkaline solution is washed with deionized water until it is neutral and ultrasonically dispersed in a certain amount of deionized water / ethanol mixed solution, and the oxygen-containing organosilicon compound is added dropwise under ultrasound; then the ultrasonicated solution is transferred to a hydrothermal reactor, reacted at 160-200° C. for 6-15 hours, the hydrothermal reaction product is filtered, and the precipitate is washed three times with ethanol and deionized water respectively, and dried in an oven to obtain a dry product; Step 3: The dried product is mixed with Mg powder in a mass ratio of 10:1, reacted at 600°C in an argon / hydrogen mixture for 4-8 hours, and the obtained mixture is washed with dilute hydrochloric acid, ethanol and deionized water respectively until neutral, and dried to obtain a treated magnesium thermal reaction product; Step 4: Ultrasonic dispersion of the treated magnesium thermal reaction product in deionized water, adding a certain amount of sodium carbonate and calcium chloride in sequence, stirring vigorously to obtain a white precipitate uniformly coated with calcium carbonate; then adding the white precipitate to a certain amount of toluene solution of mosaic mesophase asphalt, stirring for 24 hours, filtering, washing with deionized water and drying; placing the dried precipitate in a tubular furnace, pre-oxidizing at 300°C in air atmosphere for 2-4 hours, and carbonizing at 800-1000°C in argon atmosphere for 2 hours to obtain a carbonized product; Step 5: Place the carbonized product in 0.1 mol / L hydrochloric acid, wash thoroughly to remove calcium carbonate precipitate, then wash with deionized water until neutral, and dry to obtain an embedded mesophase asphalt-based silicon-carbon composite electrode material having a four-level core-shell structure of "carbon-void-silicon-carbon".

2. The modification preparation method of a mosaic mesophase pitch-based silicon-carbon composite electrode material according to claim 1, characterized in that: The mosaic mesophase asphalt refers to a petroleum-based mosaic mesophase asphalt in which the radius of anisotropic substances in the asphalt is distributed between 5 and 8 microns.

3. The modification preparation method of a mosaic mesophase pitch-based silicon-carbon composite electrode material according to claim 2, characterized in that: The average anisotropy radius in the mosaic mesophase pitch is 7.5 microns.

4. The modification preparation method of a mosaic mesophase pitch-based silicon-carbon composite electrode material according to claim 1, characterized in that: The organic strong base is selected from one of potassium tert-butoxide, sodium tert-butoxide or tetramethylguanidine; The oxygen-containing organic silicon compound is selected from one of triisopropylsilyl trifluoromethanesulfonate, 3-tert-butyldimethylsilyl-2-propyn-1-ol or (1,1-dimethylethyl)dimethylsilyl trifluoromethanesulfonate.

5. The modification preparation method of a mosaic mesophase pitch-based silicon-carbon composite electrode material according to claim 1, characterized in that: The amount ratio of the ball-milled embedded mesophase asphalt to the oxygen-containing organosilicon compound is 1g:(0.2-0.6)g.

6. The modification preparation method of a mosaic mesophase pitch-based silicon-carbon composite electrode material according to claim 1, characterized in that: The molar ratio of sodium carbonate to calcium chloride is 1:1, and the mass ratio of the magnesium thermal reaction product to sodium carbonate is 3:

1.

7. The modification preparation method of a mosaic mesophase pitch-based silicon-carbon composite electrode material according to claim 1, characterized in that: The heating rate of the air atmosphere pre-oxidation process is 1℃ / min.

8. The modification preparation method of a mosaic mesophase pitch-based silicon-carbon composite electrode material according to claim 1, characterized in that: In the embedded mesophase asphalt-based silicon-carbon composite electrode material, the thickness of the silicon layer is 0.03-0.1 μm, the thickness of the void structure is 0.02-0.1 μm, and the thickness of the external carbon layer is 0.02-0.1 μm.

9. The modification preparation method of a mosaic mesophase pitch-based silicon-carbon composite electrode material according to claim 1, characterized in that: The method for preparing the solution of the embedded mesophase asphalt is to dissolve the embedded mesophase asphalt in a solvent, wherein the solvent is selected from one or more of tetrahydrofuran, toluene, N-methylpyrrolidone, and pyridine; the amount ratio of the solvent to the embedded mesophase asphalt is 200mL: (0.5-1.5)g.

10. A mosaic mesophase pitch-based silicon-carbon composite electrode material, characterized in that: The electrode material is prepared by the modification preparation method described in any one of claims 1 to 9, and has a first-cycle coulombic efficiency of more than 70%, a reversible specific capacity of more than 550 mAh / g at a current density of 0.1C, and a specific capacity of more than 400 mAh / g at a high current density of 10C.

Citation Information

Patent Citations

  • Modified microcrystal graphite cathode material of lithium ion battery as well as preparation method and application thereof

    CN107814383A

  • Efficient preparation method of intermediate phase pitch carbon microspheres

    CN111960408A